ONTOLOGICAL MODEL OF A DATABASE OF INFORMATIONEDUCATIONAL PORTAL OF THE UNIVERSITY - Toxanov, S.; Abzhanova, D.; Faizullin, A. (Scientific Journal of Astana IT University, 2022)
According to the state program “Informational Society 2030”, it is planned to develop education on the basis of new progressive concepts of introducing the latest information technologies and scientific and methodological achievements into the educational process. In order to achieve goals, it is necessary to implement mobilization and effective use of staff and property and technical resources of the university. It is possible if there is purposeful modeling of the information and educational portal of the university. The choice and design of teaching technology are primarily determined by the type of students’ competencies and the characteristics of the planned learning outcomes for each level of competence (knowledge, skills, and experience). Constant improvement of EP content and educational technologies as a key factor of education services quality is a vital demand. The article considers the issues of the concept of ontology, IDEF-technologies and, based on the ontological model proposed in the article, the architecture of the database of the information and educational portal of the university is developed and classes and properties for the implementation of this model are defined, and a functional model of the university in IDEF0 is developed, which covers all types of university activities, integrates all information flows and forms a single information space.